Analisis Pemanfaatan LMS (Learning Management System) Pada UPBJJ-UT Jambi - Syifqi, Achmad; Kurniabudi, Kurniabudi (LPPM Universitas Dinamika Bangsa, 2023)
Universitas Terbuka (UT) utilizes E-Learning to support its learning services commonly referred to as tutorials. In supporting the implementation of this tutorial, UT created a web-based application called LMS (Learning Management System) application. This application is a companion for tutorial activities. When monitoring tutorials, there are still many students who say that they have not fully used this application. Until now, there has never been research and evaluation and analysis of the perception of acceptance of LMS applications, especially for Pendas program students. This research aims to analyze what factors influence the level of acceptance and use of E-Learning. This research model uses Technology Acceptance Model (TAM) theory. Data analysis uses Partial Least Square method on Structural Equation Modeling (PLS-SEM) by using SmartPLS software as the research model. The number of respondents was 290 students, consisting of students majoring in PGSD and PGPAUD at UPBJJ-UT Jambi. The results of this study showed six of the seven hypotheses showed positive and significant results and only one hypothesis was rejected or insignificant. This shows that the LMS application has a positive and significant influence in helping students in tutorial activities.